Plasma oncology: Adjuvant therapy for head and neck cancer using cold atmospheric plasma - Li, Xuran; Rui, Xiaoqing; Li, Danni; Wang, Yanhong; Tan, Fei (Frontiers in Oncology, 2022)
The worldwide incidence of head and neck cancer (HNC) exceeds half a million cases annually, and up to half of patients with HNC present with advanced disease. Surgical resection remains the mainstay of treatment for many HNCs, although radiation therapy, chemotherapy, targeted therapy and immunotherapy might contribute to individual patient’s treatment plan. Irrespective of which modality is chosen, disease prognosis remains suboptimal, especially for higher staging tumor. Cold atmospheric plasma (CAP) has recently demonstrated substantial anti-tumor effect. After thorough PubMed search, we provide a comprehensive review depicting the oncological potential of CAP in HNC treatment. We discovered that CAP is applicable to almost all categories of HNC, including upper aerodigestive tract cancers, head and neck glandular cancers and skin cancers. In addition, CAP is truly versatile, as it can be applied not only directly for superficial or luminal tumors but also indirectly for deep solid organ tumors. Most importantly, CAP can work collaboratively with existing clinical oncotherapies with synergistic effect. After our attempts to elaborate the conceivable molecular mechanism of CAP’s anti-neoplastic effect for HNC, we provide a brief synopsis of recent clinical and preclinical trials emphasizing CAP’s applicability in head and neck oncology. In conclusion, we have enunciated our vision of plasma oncology using CAP for near future HNC treatment.